EFEKTIVITAS PENGAJARAN REMEDIAL UNTUK MENINGKATKAN KETUNTASAN BELAJAR SISWA : StudiEksperimenpada Mata Pelajaran IPA Kelas VIII di SMP N 1 Kasomalang - Zulkaedah, Romlah (2014)
Penelitianinidilatarbelakangiolehrendahnyapencapaianketuntasanbelajarsiswabaiksecaraindividuatauklasikalpadamatapelajaran IPA.Melaluipenelitianinidikajipermasalahanpengajaran remedial bagaimana yang akanmeningkatkanketuntasanbelajarsiswadalammatapelajaran IPA di SMP. Tujuanpenelitianadalahuntukmengujiadaatautidaknyapeningkatanketuntasanbelajarsiswasetelahditerapkanpengajaran remedial berdasarkankesulitanbelajarpadamatapelajaran IPA di kelas VIII.Penerapanpengajaran remedial tesebutdiharapkandapatmeningkatkanketuntasanbelajarsiswa.Untuk membuktikan hipotesis, penelitianinimenggunakanmetodequasi-experimentaldengannonequivalent-group pretest-posttest design.Penelitiandilaksanakan di SMP Negeri 1 Kasomalangdengan target sample sebanyak 42 orang yang terbagi 2 kelompokyaitu, kelompokeksperimendankelompok control. Data diperolehdengancaramenerapkanbeberapaistrumenyaitusoaltes, angketdanobservasi. Berdasarkanhasilpretestdiperolehbahwasiswamengalamikesulitanbelajarpadaranahkognitifaspekpemahaman (C2) danpenerapan (C3), makapengajaran remedial yang dilaksanakanadalahpengajaran yang mengarahpadapenguatankonsepdanmemperbanyaklatihansoal.Metodatersebutmerupakansalahsatuupayauntukmemperbaiki proses danhasilpembelajaran IPA. Setelahpenelitiandilaksanakandiperolehfakta yang menunjukanadanyapeningkatanketuntasanbelajarsiswaberdasarkan diagnosis kesulitanbelajar.Hal tersebutdibuktikandenganhasil rata-rata gain kelompokeksperimenlebihbesar, yaitu 0,779 dibandingkanhasil rata-rata gain kelompokkontrol, yaitu 0,445.Hasiltersebutmembuktikanbahwapengajaran remedial berpengaruhpositifmembuatpemahamansiswabertambah. The background of this study is the lowness of students' learning thoroughness achievement whether it is individual or clasical on science lesson. Through this study, it has been investigated the problem on what kind of teaching remedial that will improve students' learning thorougness on science lesson at junior high school. Aim of this study is to examine if there is improvement on students' learning thoroughness or not after remedial teaching is implemented based on learning difficulties on science lesson in VIII graders.The implementation of remedial teaching is expected to improve students' learning thoroughness. In order to prove the hypothesis, this study uses quasi-experimental method with nonequivalent-group pretest-posttest design. This study is conducted at SMP Negeri 1 Kasomalang with 42 students as the target sample which is devided into two groups, experimental group and control group. The data was taken by implementing some instruments, those are test questions, questionaires, and observation. Based on the result of the pretest, it has been obtained that students face learning difficulties on cognitive domain in comprehensive aspect (C2) and implementation (C3), so remedial teaching in this case is focused on strengthening concept and doing more practices. This method is one of ways to make the proccess and result of science lesson better.After the study is conducted, it is obtained a fact that shows the improvement of students' learning thoroughness based on students' learning diagnosys. This is proved by the result of average gain of experiment group is bigger, that is 0.779 compared to average gain of control group, that is 0.445. Those results prove that remedial teaching has positive impact in improving students' understanding.